2021
DOI: 10.18632/aging.203097
|View full text |Cite
|
Sign up to set email alerts
|

CXCR5 induces perineural invasion of salivary adenoid cystic carcinoma by inhibiting microRNA-187

Abstract: CXCR5 played critical roles in tumorigenesis and metastasis. Nevertheless, little was known about the involvement of CXCR5 in perineural invasion (PNI) of salivary adenoid cystic carcinoma (SACC). Here, we confirmed upregulation of CXCR5 in SACC specimens and cells and identified that CXCR5 exhibited a significant positive correlation with PNI. Functionally, knockdown of CXCR5 suppressed SACC cells migration, invasion and PNI ability, whereas CXCR5 overexpression displayed the opposite effects. Moreover, CXCR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…not specified) SACC-83, SACC-LM [ 36 ] 10. miR-187 18q12.2 Suppress SACC cell migration, invasion, and PNI ability by targeting CXCR5 CXCR5 ↓ 8.00 158 SACC patient's tissue samples 20 cases of normal salivary glands (NSG) SACC-LM [ 37 ] NA- Not Available ↓ - Downregulation. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…not specified) SACC-83, SACC-LM [ 36 ] 10. miR-187 18q12.2 Suppress SACC cell migration, invasion, and PNI ability by targeting CXCR5 CXCR5 ↓ 8.00 158 SACC patient's tissue samples 20 cases of normal salivary glands (NSG) SACC-LM [ 37 ] NA- Not Available ↓ - Downregulation. …”
Section: Methodsmentioning
confidence: 99%
“…A recent study done by Zhang et al. found that C-X-C chemokine receptor type 5 (CXCR5) induces tumor cell differentiation into Schwann-like cells by suppressing miR-187, which disinhibited S100 Calcium Binding Protein A4 (S100A4)and hence facilitated SACC perineural invasion (PNI) [ 37 ]. To understand the involvement of miRNA in CXCR5-induced PNI of SACC, researchers used miRNA array analysis and TargetScan to anticipate possible target relationships.…”
Section: Diverse Mirnas Affecting Sacc Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR5 + CD8 T cells correlate with disease-free or overall survival in pancreatic, colon, follicular lymphoma, gastric, high-grade serous ovarian, hepatocellular, and bladder cancers and thus is considered a potential biomarker ( 15 , 17 , 20 , 23 , 25 , 26 ). On the contrary, decreases in disease-free survival in non-small cell lung and salivary adenoid cystic carcinomas are associated with infiltrating CXCR5 + CD8 T cells ( 74 , 75 ). Functional studies beyond correlative data and mRNA expression remains lacking as to how these cells benefit or negate a tumor microenvironment.…”
Section: Could Cxcr5 + Cd8 T Cells Initiate the De...mentioning
confidence: 99%